Peningkatan Kemampuan Berpikir Kritis, Kemampuan Pemecahan Masalah dan Minat Belajar Siswa Dengan Board Game di SMA Kristen 1 Tomohon - Rangian, Stevani Caroline; Estafianto, Hary Dwi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the relationship between eye-foot coordination This study aims to determine: 1) the results of developing the board game "Asyiikounting" as accounting learning media: 2) the feasibility of the Board Game "Asyiikounting" as a learning media for Accounting based on the assessment of material experts and media experts and students; 3) analysis of the improvement students' critical thinking skills, problem-solving skills, and students interest before and after using the "Asyiikounting" Board Game in class XII IPS SMA Kristen 1 Tomohon. This research is a development research model of Borg & Gall. The data was collected through documentation, questionnaires and measuring the post-test- pre-test. The results showed that: 1) “Asyiikounting” Board Game is feasible to use; 2) Validation of the "Asyiikounting" Board Game from the material expert is “feasible”, media expert is “very feasible” and students is “feasible”; 3) Using Board Game "Asyiikounting" in accounting learning significantly can improve critical thinking skills, problem solving skills and student interest. So the conclusion is using Board Game "Asyiikounting" effective support learning activities.